Alternative Globalisations and the Role of China’s Secondary Cities: Three Case Studies - Wang, Qianyi; Li, Ran; Cheong, Kee Cheok (National University of Singapore, 2019)
Globalisation has arguably been the most discussed topic since the 1970s, and the intensity of discussion peaked in 1995 when the World Trade Organization was formed. As the ideal for growth, globalisation was the tide that lifted all boats. China has been held up as a shining example of a beneficiary of globalisation. The China globalisation model, exemplified by Shenzhen, is founded on production for exports, with inflow of foreign direct investment by transnational corporations bringing in technologies and efficient production methods. The authors analyse case studies of secondary cities, namely Quanzhou, Yiwu and Nanning, to illustrate that alternative globalisation models exist. Quanzhou has had a long history of globalisation, the nature of which changed over the centuries. Its globalisation today leverages the history of earlier phases. The Yiwu model is a contrast to the Shenzhen model in that Yiwu’s globalisation represented an extension of its role as a wholesale market benefiting the small traders. Nanning is a good example of state-led globalisation. Findings have demonstrated that other models undoubtedly exist, and that city size is not necessarily indicative of the impact of globalisation. © China: An International Journal.